IMPLEMENTASI METODE TOTAL PHYSICAL RESPONSE (TPR) DALAM MENINGKATKAN HAFALAN KOSA KATA BAHASA ARAB SISWA KELAS XI N DI MAN 4 JOMBANG - M Hafis Fatahillah; Abdul Qodir (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study aims to examine the implementation of the Total Physical Response (TPR) technique in optimizing the memorization of Arabic vocabulary (mufrodat) of class XI N students at MAN 4 Jombang. The TPR technique is a language learning strategy that combines verbal instructions with physical responses, resulting in a dynamic and enjoyable learning atmosphere. Through a qualitative descriptive strategy, information collection is carried out through observation, interviews, and documentation. The research output shows that the implementation of the TPR technique is able to optimize students' memorization abilities for mufrodat, produce an interactive classroom atmosphere, and make students more dynamic in the learning process. However, there are obstacles such as the less than optimal use of this technique during afternoon lessons and limitations in teaching abstract vocabulary. This research provides an important contribution to the development of contextual and enjoyable Arabic language learning strategies, especially in terms of vocabulary mastery.